Analisis Efektivitas Program Edukasi Produk Syariah bagi Nasabah di Bank BJB Syariah KCP Lippo Cikarang - Abdul Rojak; Dudang Gojali (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This study aims to analyze the effectiveness of the sharia product education program organized by Bank BJB Syariah KCP Lippo Cikarang to its customers. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with customers and bank employees, observations, and documentation related to the implementation of the education program. The results of the study indicate that the sharia product education program is able to increase customer understanding and awareness of the sharia products offered. However, several obstacles were found such as limited implementation time, lack of interactive educational materials, and low active customer participation. This study recommends the need for innovation in education methods and increased collaboration between banks and customers to increase the effectiveness of sharia product education programs in the future.